The utilization of aerial potato (Dioscorea bulbifera) - Marca, Daisy E. Masana
The study, "The Utilization of Aerial Potato" (Dioscorea bulbufera) was conducted at the Food Science Department of the Don Severino Agricultural College, Indang, Cavite from January to March, 1996. It aimed to investigate the utilization and acceptability of different food products from aerial potato, threby determining the technology for utilizing the materials for staple, vegetable, snacks and dessert. specifically, answers to the following questions were sought: A. 1. Can aerial potato be acceptable as substitute for staple food if found edible? 2. Which of the different proportions of aerial potato will be most acceptable as vegetable in menudo in terms of color, odor, flavor, off-flavor and general acceptability? 3. Which of the two snack foods prepared from aerial potato will produce the best product as to color, odor, flavor, off-flavor, texture, crispiness and general acceptability? 4. Which of the different proportions of aerial potato flour will produce the best product as polvoron in terms of color, odor, flavor, texture, off-flavor and general acceptability? B. What is the nutritive value of aerial potato? C. What are the minerals present in aerial potato? Using experimental design, a structured score cards were used to gather the necessary data. Data on sensory analysis were subjected to Analysis of Variance (ANOVA), percentage and mean scores were compared using Duncan's Multiple Range Test (DMRT). The sensory evaluation revealed that aerial potato is acceptable as substitute for staple in terms of color, flavor, texture, odor, off-flavor, juiciness and general acceptability. When utilized as vegetable in menudo, color of aerial potato showed no significant differences among treatments with mean ratings of 3.300; 3.300; and 2.900 in 100% (T1) aerial potato; 75% (T2) aerial potato; and 25% (T3) aerial potato, respectively. The odor of 100% aerial potato (T1) differed significantly with 25% aerial potato (T3). But the odor of menudo with 75% (T2) aerial potato is significantly the same with the odor of 100% (T1) and 25% (T3) aerial potato. In terms of flavor, aerial potato in different proportions (100%, 75%, and 25%) was significantly the same which was considerable. The off-flavor of aerial potato in menudo in different proportions were significantly the same. The general acceptability of aerial potato in different proportions as vegetable in menudo showed no significant difference with each other which means that aerial potato is acceptable as vegetable in menudo. As snacks, French Fries were rated acceptable in terms of color, flavor, texture, odor, and general acceptability. In terms of flavor, majority (90%) of the respondents replied that off-flavor in French fries was moderately imperceptible. In terms of crispiness, majority (80%) of the taste panel responded that aerial potato as french fries was neither crispy nor tough. As chips, color differed significantly according to different proportions. The color of 100% (T1) aerial potato was significantly different with color of 25% (T3) aerial potato. But color of 75% (T2) aerial potato showed no significant difference from 100% (T1) aerial potato. The odor of chips did not have significant differences from the other treatments with mean ratings of 3.6, 3.3, and 3.5 for proportions 1, 2 and 3, respectively. The flavor of chips according to different proportions of aerial potato were significantly the same. In terms of crispiness, chips from 100% (T1) aerial potato obtained the highest mean rating of 4.100 which showed its acceptability. In terms of general acceptability, chips prepared from different proportions of aerial potato were acceptable. As dessert, polvoron from 25% aerial potato flour (T3) produced the best product as to color, flavor, texture and general acceptability. While odor and off-flavor in different proportions were significant the same. In general, serial potato is acceptable as substitute for staple food. It can also be utilized as vegetable in meat recipes, likewise, French Fries and chips can also be developed from aerial potato and twenty five percent (25%) aerial potato flour can be used in the production of polvoron. High amount of food energy or calories is present in aerial potato and increases as stored. It also contains ash, crude fat, crude protein, total carbohydrates and crude fiber in lower amounts. Aerial potato can be utilized as an alternative and as staple food since it is an energy giving food. It could also be a potential crop for snacks and may be considered as important as other root crops in the production of flour. Aerial potato contains calcium, magnesium and iron which are necessary in the recommended dietary allowance (ROA). However, it contains lead (Pb) at 7.49 ppm. The Bureau of Food and Drug has no available data nor reference as to the tolerance limit of lead in aerial potato.